Synthesis and Characterization a New 1,3-Diazepine Compounds from New Bis 4-Amino-3-Mercpto-1,2,4-Triazole Derivatives - Younus, Atyaf AQ; Jber, Nasreen R (Al-Nahrain Journal of Science, 2017)
Compounds with two triazole rings IVa,b were synthesized through the reaction of diacid hydrazide firstly with CS2/KOH, and secondly with excess of hydrazine hydrate. The one-step reaction of isatin with benzylidene benzeneamine (S1–S10) in ethanol gave 2-Ar-3- Ar’[3,4b][1,3]benzodiazepine-4,5-diones (D1-D10) in good yields. The products were characterized using FTIR, 1HNMR spectroscopy and CHN elemental analyses.